INVESTIGATING THE INFLUENCE OF ONLINE REVIEWS ON CONSUMER PURCHASE DECISIONS IN THE ONLINE FOOD DELIVERY INDUSTRY - Jain, Shalini; Singh, Jagrati; Satsangi, Akshay Kumar (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Food delivery, fast-growing online, has led many consumers to change how they buy meals, mainly because of how easy it is with online platforms. When deciding what to purchase, many people rely on online reviews more than on many other sources. Although there is a huge amount of consumer-generated content, the online food delivery field has not been studied much in terms of how online reviews influence purchase decisions. This paper attempts to fill the gap by creating and validating a scale that measures the impact of online reviews in this unique setting. Online reviews are explained in terms of both Information Processing Theory and the principle of social proof. It explains how individuals get, make sense of and use website data while shopping, showing that a clear and credible website has a positive impact on users. In uncertain settings, people tend to rely on others’ comments when taking a decision which is why online feedback is extremely important for forming consumer trust. Things that play a role in guiding consumer purchase choices are credibility of the reviewer, the general tone and amount of feedback, how clearly the language makes ideas and how relevant the reviews are to the situation of each consumer. When taken together, these dimensions fully explain how online reviews impact a buyer’s intention to purchase. The age, gender and history with online food orders of those reading reviews can alter how their response to reviews. Marketers must notice these effects to design strategies that suit all types of consumers.